Taxonomic Status of the Streaked Saltator, Saltator striatipectus (Passeriformes: Thraupidae), from Puná Island, Ecuador - Freile, Juan; Bonaccorso, Elisa; Amigo, Xavier; Cadena-Ortiz, Héctor; Navarrete, Ronald; Amigo, Zoé; Piedrahita, Paolo; Chaves, Jaime A. (Zootaxa, 2018)
The Streaked Saltator, Saltator striatipectus, is an uncommon to common resident of open areas, cultivated land, gardens, and forest edges, with ten subspecies recognized from west Costa Rica through west Peru (Brewer 2016). Patterns of plumage variation, especially mantle color and streaking pattern below, are complex across subspecies and age classes (Chapman 1926; Ridgely & Tudor 2009; Brewer 2016). Until recently, S. striatipectus was considered conspecific with the Lesser Antillean Saltator S. albicollis, but separated on the basis of genetic differentiation despite overall plumage similarities (Seutin et al. 1993). Actually, S. striatipectus and S. albicollis are not each other’s closest relatives (Chaves et al. 2013).